Building Comprehensive Sex Education Plans for Teenagers: Groundwork-Based Research Design Application - Le Quyen, Tran Thi; Hanh Luu, Bui; Thu Thao, Le Thi (KnE Social Sciences, 2023)
Although sexual education is an important part of a child’s education and upbringing, in Vietnam, sex education is not an official subject in school, and young people’s awareness of Comprehensive Sex Education (CSE) is still limited. While sex education at school is necessary, it is not the only way nor sufficient enough to change teenage sexual behavior. A parent’s role could involve communicating about values, providing a positive family environment, and monitoring their children’s behavior. This topic explores the awareness of teenagers about CSE and the availability of teaching CSE in Vietnamese schools and families. Data was collected via an online survey of 89 teenagers and 119 parents whose children are teenagers. The findings revealed that the target group is not fully aware of CSE and in particular, they also feel the importance of the family in this regard but are afraid to share gender issues with their parents and tend to find information on their own through the internet. Keywords: teenagers, sex education, reproductive health, Vietnam, sex and sexuality